RC time (resistance × compliance) is related to residual symptom after pulmonary endarterectomy in chronic thromboembolic pulmonary hypertension. (June 2022) - Yanaka, Kenichi; Nakayama, Kazuhiko; Taniguchi, Yu; Onishi, Hiroyuki; Matsuoka, Yoichiro; Nakai, Hidekazu; Okada, Kenji; Shinke, Toshiro; Emoto, Noriaki; Hirata, Ken-ichi
Abstract: Background: Right ventricular (RV) afterload is widely assessed by pulmonary vascular resistance (PVR). However, RV afterload is underestimated because PVR does not account for the pulsatile load. The pulsatile load is often evaluated by pulmonary arterial compliance (PAC). The RC (resistance-compliance) time, which is calculated from the product of PVR and PAC, is considered to remain constant under medical therapy. However, little is known on how RC time is affected by invasive therapy in chronic thromboembolic pulmonary hypertension (CTEPH). This study aimed to evaluate change of RC time in patients underwent pulmonary endarterectomy (PEA). Furthermore, we investigated the clinical relevance of RC time. Methods: We reviewed consecutive 50 patients except for death case underwent PEA. Baseline clinical parameters including RC time before performing PEA and follow-up were evaluated. Patients was classified as decrease or non-decrease according to change of RC time. Furthermore, we classified patients into a NYHA I group who had no symptom after treatment and a residual symptom group in order to investigate the relationship of RC time to residual symptoms. Results: RC time was significantly decreased after PEA (0.54 ± 0.16 to 0.45 ± 0.12 sec, p < 0.001). Residual symptom after PEA of Decrease group were significantly better than that of Non-decrease group in RC time (12 patients, 40% vs. 11 patients, 78.6%, p < 0.02). Furthermore, multivariate analysis revealed that only RC time after PEA was independently associated with residual symptom (OR 1.026, 95% CI 1.005–1.048; p = 0.017). Conclusions: RC time was decreased after PEA, and might be a possible indicator for predicting PEA success.